THE DEVELOPMENT OF DEFORMATION RELIEF AT PROGRAM CYCLIC LOADING - Карускевич, М.; Маслак, Т.; Капустинський, А.; Сейдаметова, Г. (Science-based technologies, 2010)
The fatigue tests of aluminum alloy D16AT have been shown that the deformation relief which is formed on the surface of clad layer under cyclic loading is sensitive to the cyclic loading regime changes. It has been noted the there is the deformation relief sensitivity to the maximum cyclic loading under transition from less to high stress level as well as from high to less stress level.